2009
DOI: 10.1007/s12548-009-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional harmony between the sagittal condylar path inclination and the anterior guidance inclination

Abstract: The determinants of the morphology of the mandibular tubercle of the Temporomandibular Joint (TMJ) have been the subject of numerous investigations but remain poorly understood.It has been hypothesized that the lingual surfaces of the maxillary anterior teeth could influence the growth, the development, and the shape of the mandibular tubercle.Nonetheless, there is disagreement concerning the existence of a functional relationship between the condylar path and the anterior guidance of the mandible.The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
2
9
1
Order By: Relevance
“…AEI values smaller than 30˚ have been characterized as fl at, while those greater than 60˚ have been characterized as steep 15 . Th e results of various studies correspond to this range and are similar to the values recorded in our study 21,[23][24][25][26][27] . In both the medieval and recent sample groups, diff erences were found between the right and left joints.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…AEI values smaller than 30˚ have been characterized as fl at, while those greater than 60˚ have been characterized as steep 15 . Th e results of various studies correspond to this range and are similar to the values recorded in our study 21,[23][24][25][26][27] . In both the medieval and recent sample groups, diff erences were found between the right and left joints.…”
Section: Discussionsupporting
confidence: 90%
“…Gilboa et al report that the AEI values usually vary from 21 to 64 degrees 21 . Koyoumdjisky 23 measured the inclination of the anterior wall of the fossa and obtained a mean value of 47.6˚, while Zoghby et al 24 found a mean value of 47.46˚ using the method of mechanical axiography in study participants. It has been reported that the normal value of AEI in adults is from 30˚ to 60˚.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars have reported that IG influences condylar guidance, which in turn modifies TMJ morphology [5,8]. Different condylar and incisal guidance ratios have been found to affect the activity of anterior and posterior temporal muscles [9].…”
Section: Introductionmentioning
confidence: 99%
“…Incisal guidance is among the occlusal factors and is essential for a harmonious and functional occlusion that can stabilise mandibular movement, reduce applied forces, and protect anatomical structures. Many researchers have emphasised that the incisal path must be coordinated with the condylar path and proposed that incisal guidance affects condylar guidance, which in turn influences condyle position and morphology [ 4 , 5 ]. Interestingly, we previously reported that the relationships between the condyle and fossa are diverse in individuals with different incisor guiding angles, and incisal guidance is related to the growth and development of the TMJ [ 6 ].…”
Section: Introductionmentioning
confidence: 99%